Agentic AI Readiness and Sustainable Service Performance in Digital Retailers - Syifa Isfahan, Amelia; Puspitasari, Diana (Inovasi Analisis Data, 2026)
Purpose: This study explore how digital and artificial intelligence (AI)based organisational capabilities relate to sustainable service performance in digital retail companies, via operational agility mechanisms. Method: This paper adopted a quantitative research methodology with survey data collected from digital retailers' managers and with the help of partial least squares approach to structural modeling. Findings: The results demonstrate that the use of customer analytics, data quality capability, and process digitization are directly as well as positively associated with sustainable service performance through operational agility. This is a key factor in the successful translation of digital strengths into better service results, which requires agility for operational and processes change and to make quick decisions. By contrast, the influence of agentic artificial intelligence capability on service performance is not statistically significant, suggesting that high-level AI technologies are not enough to create value unless well-integrated into the organization. Additionally, data governance maturity does not enhance the relationship between operational agility and service performance, indicating that governance is mostly an enabler infrastructure rather than a performance enhancer. Novelty: Our contribution to the literature is therefore three-fold in unpacking artificial intelligence capability, analytics use and process digitization from a single resource-based dynamic capabilities perspective, while providing nuanced evidence within the digital retail context. Implications: Findings empirically contribute to strategic managerial recommendation that managers need to prioritize agility based digital investments, and theoretically how service performance sustainability develops line of the orchestration of data, technology, and operational capabilities in dynamic markets.